PENGARUH BUDAYA TERHADAP PERBEDAAN SISTEM/PRAKTEK AKUNTANSI DAN PROSES HARMONISASI STANDAR AKUNTANSI INTERNASIONAL - KHOMSIYAH KHOMSIYAH (Jurnal Bisnis dan Akuntansi, 2001)
This paper considers the impact of culture on accounting practices. The studyof culture and cultural dimension by Hofstede (1980) is reviewed, together with the application of these ideas to accounting, particularly in the work of Gray (1988) and Perera (1989). This paper also attempts to explain the harmonization of accounting standards, which is developed by The International Accounting Standards Committee (IASC), especially for inflation accounting standard.